2022
DOI: 10.3389/fonc.2022.907975
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Prognostic Nomograms After UTUC Surgery

Abstract: BackgroundCurrent guidelines recommend assessing the prognosis in high-risk upper tract urothelial carcinoma patients (UTUC) after surgery. However, no specific method is endorsed. Among the various prognostic models, nomograms represent an easy and accurate tool to predict the individual probability for a specific event. Therefore, identifying the best-suited nomogram for each setting seems of great interest to the patient and provider.ObjectivesTo identify, summarize and compare postoperative UTUC nomograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In addition, to our best knowledge, there is no fall risk assessment scale that specifically targets the elderly with visual impairment to highlight the high-risk groups. Prediction models and nomograms based on predictors/risk factors of diseases can provide patients with accurate prediction tools to be used in safety management for individuals ( 43 45 ). We contributed a predictive model and nomogram based on these abovementioned risk factors for falls, and older patients with visual impairment may get a predicted probability of fall based on the total score axis of the nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to our best knowledge, there is no fall risk assessment scale that specifically targets the elderly with visual impairment to highlight the high-risk groups. Prediction models and nomograms based on predictors/risk factors of diseases can provide patients with accurate prediction tools to be used in safety management for individuals ( 43 45 ). We contributed a predictive model and nomogram based on these abovementioned risk factors for falls, and older patients with visual impairment may get a predicted probability of fall based on the total score axis of the nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…Current risk stratification for UTUC is based on clinical and pathologic features [ 1 ]. However, these models suffer from moderate discrimination and a lack of external validation [ 24 ]. Discovery of clinically useful biomarkers and their addition to current predictive models is the new frontier in the era of personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as updated recent multicenter study by ROBUUST group ( 31 ), robotic and laparoscopic surgery group showed comparable oncological outcomes. Recent systemic review and meta-analysis demonstrate that advanced tumor stage and lymphovascular invasion as the most prognostic factor for overall survival ( 32 ). Our cohort also showed consistent result, and we additionally found that B2-MG could be a novel prognostic factor having the comparable prognostic power with above two factors.…”
Section: Discussionmentioning
confidence: 99%